The impact of National Health Insurance online referral system on the access and quality of health services in Gianyar District, Bali, Indonesia - Ida Ayu Agung Dewi Sawitri; Pande Putu Januraga; Ni Made Sri Nopiyani (Universitas Udayana, 2020)
Background and purpose: The introduction of an online referral system aims to improve the quality and costs control of the National Health Insurance (NHI) or Jaminan Kesehatan Nasional. This study aims to determine the impact of the NHI online referral system implementation on access and quality of health services in Gianyar District. Methods: This is an explorative qualitative study conducted in Gianyar, Bali, Indonesia. Data was collected through semistructured in-depth interviews to a total of 26 informants recruited purposively. They were including policy makers in the health office and the NHI implementing organization (BPJS), heads of public health centres (puskesmas), private health facilities and referral healthcare facilities; and 13 NHI participants. Data collection was undertaken from May to August 2019. The interview results were thematically analysed based on the Health Care Reform Control Knobs Framework. Results: The study identifies several positive impacts of the online referral system, which include: the closer distance of patients accessing services, the easier it is to obtain information on services at referral health facilities, and the easier the hospital to promote its service products, the higher assurance of patients being accepted by the referral hospitals, patients with special conditions are better accommodated, the easier the administrative procedure, improved time, cost and working procedure efficiencies, increased punctuality of the services, and guaranteed data security that reduces the risk of lost or damaged referral documents. On the other hand, the online referral system has also resulted in negative impacts, some of them were system inconsistencies, information and communication technology (ICT) constraints, service discontinuity, service injustices and loss of patients’ loyalty. Conclusion: NHI online referral system generally have positive impacts on access and quality of health services, however, it is necessary to improve several aspects of the online referral system to better accommodate user needs and to optimize service.